A Base Nacional Comum Curricular em questão - Rodrigues, Vivian Aparecida da Cruz (2017)
Since 2015, the Brazilian Ministry of Education, together with other institutions, particularly the Brazil's National Board of Secretaries of Education and the National Union of Municipal Directors of Education have proposed to write up a paper entitled: Curricular Common National Basis (CCNB) to the Brazilian Education system and to spread out its version to the community by electronic means. That is the most current proposal of the Brazilian Ministry of Education and its relevance is yet questionable in the educational area, although it is not a new one; in previous time, it was already announced and, including, it should be suggested some ideas on an elaboration of a national basis, but such negotiations no longer exist on the achievement of the two presented introductory versions. Facing the main noticed problem in education which is the absence of clarity in the educational and academic circles, about the negotiation and the elaboration of a basis, we sought after on the research to amplify the comprehension on the negotiation process and the elaboration of the curricular common national basis in the Brazilian Educational System from the two versions presented. Therefore, it was observed the elaboration of a curricular common basis in the history of national curriculum and some external curriculum frameworks; it has been studied the structures of the CCNB texts – 1st e 2nd versions, specifically in the introductory fragments, some technical views were analyzed from the official peer-review committee, taking into consideration their critics to the first preliminary version. Authors as Gimeno Sacristán (1998, 2000, 2013), Apple (2006), Arroyo (2013), Jurjo Santomé (2013), Chizzotti and Ponce (2012), Libâneo (2012), Cury (2014), Alves (2014), Macedo (2014, 2015, 2016) , Lima Verde (2015), among others were the scope of the theoretical foundation of this work, besides the official papers from the Brazilian Ministry of Education. It was noticed a long step forward related to the offered text of one version to another, but, the negotiation was over delayed about the structure of a paper that could be considered a national Basis and it was not contemplated by the responsible authorities